2021
DOI: 10.1177/02557614211050986
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and psychological distress: Music listening as a coping strategy for pre-service kindergarten teachers

Abstract: Against the backdrop of the worldwide spread of COVID-19, this study aims to validate a model for coping with psychological distress and examine the effect of music listening, as a coping strategy, in moderating and lessening the effects of stressors on psychological distress. Based on 198 returned questionnaires from preservice kindergarten teachers, this study suggests students experienced such common mental health issues as stress, anxiety and depression due to the COVID-19 pandemic. Time pressures, general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nevertheless, within the date range of the scoping study, only one article examined preservice teachers’ psychological health during the pandemic. Clearly, the issue has not attracted much research attention despite the recognized impact of stress on learning (Kong & Wong, 2021 ). Kong and Wong ( 2021 ) aimed to validate a model that offered a strategy to cope with psychological distress by examining the efficacy of listening to music in moderating and lessening the impact of stressors on psychological well-being.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, within the date range of the scoping study, only one article examined preservice teachers’ psychological health during the pandemic. Clearly, the issue has not attracted much research attention despite the recognized impact of stress on learning (Kong & Wong, 2021 ). Kong and Wong ( 2021 ) aimed to validate a model that offered a strategy to cope with psychological distress by examining the efficacy of listening to music in moderating and lessening the impact of stressors on psychological well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the issue has not attracted much research attention despite the recognized impact of stress on learning (Kong & Wong, 2021 ). Kong and Wong ( 2021 ) aimed to validate a model that offered a strategy to cope with psychological distress by examining the efficacy of listening to music in moderating and lessening the impact of stressors on psychological well-being. Studies have often claimed that listening to music plays a prominent moderating role in the relation between stressors and psychological distress, but Kong and Wong found that this was not universally the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many situations during the pandemic were more difficult for music teachers and students than usual, which in turn caused some emotional or physical tension. Research (Kong & Wong, 2021;Miksza et al, 2021;Potter, 2021) revealed that the stress for music teachers was due to a heavy workload and a lack of control over equipment and performance. In addition, during the pandemic, teachers experienced few positive emotions, less involvement, and a lack of accomplishment.…”
Section: The Stress and Well-being Of Music Teachers And Studentsmentioning
confidence: 99%
“…Understanding the elements that lead to burnout and paying attention to personal feelings can help music teachers respond to stress and take a rest on time if they feel tense (Napoles, 2022). Making music by using different strategies helps music teachers experience less anxiety (Merve et al, 2021) while listening to music can regulate psychological discomfort (Kong & Wong, 2021). To make students feel good, teachers can create a virtual space where students can share their emotions and encourage each other, create an exciting learning experience and a supportive socio-emotional learning environment, and take care of their needs and listen to them (Liu, 2021b).…”
Section: The Stress and Well-being Of Music Teachers And Studentsmentioning
confidence: 99%